The Climate Change Crisis Solutions and Adaption for a Planet in Peril - Pink, Ross Michael (Springer International Publishing, 2018)
This book explores how the world community will respond to the unfolding humanitarian crisis caused by climate change. It recognises climate change as the greatest threat to human development in the 21st century, bringing with it: flooding, drought, extreme temperatures, health crises, threats to human security and severe harm to economic development. The Climate Change Crisis addresses climate change and its impact as a major threat for countries around the world. Through a collection of interviews with leading environmentalists and exploration into new innovations that can offer hope and protection for billions of people, this book presents an interdisciplinary approach towards understanding the paramount health and development challenges of climate change. This timely and informative book cuts across several disciplines, including human rights, public policy, international relations, national refugee policy, and migration studies.